The components of the jumps in expert and intermediate water polo players - Gobbi, M.; D'Ercole, C.; D'Ercole, A.; Gobbi, F. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study is to show the different multifactorial structure of jump capacity in expert and intermediate water polo players, using the principal component analysis (PCA) and multiple regression. We adopted the Teknotrain3, an instrument that enabled us to measure maximal height out of the water and dynamic components such as force, velocity, and power. The experts showed high levels of power (t = 2.75, p < 0.04) and velocity (t = 4.4, p < 0.007) with a considerable maximal height (mh) (t = 2.73, p < 0.04), whereas the intermediate players showed only an average velocity and mh and an inverse relation between power, velocity, and temporal variability in jumps, r = -0.89 (p <0.01) and r = -0.94 (p < 0.01). The intermediate players need a physical preparation of resistance training aimed at developing rapid rate of force development (RFD) and the maximal dynamic force and power and reducing temporal variability.